From Government to Regulatory Governance - Bortolotti, Bernardo (World Bank, 2012)
This article reviews the state of thinking on the governance role of public ownership and control. Optimal governance systems depend on the path of institutional development. Nevertheless, the transfer of operational control over productive assets to the private sector often yields a desirable governance system, because it may be more difficult for citizens to constrain political abuse than for governments to regulate private activity. In weak institutional environments, however, the process needs to be structured to avoid capture of the regulatory process. The speed of transfer should be matched to progress in developing a strong regulatory governance system, to which certain residual rights of intervention must be vested. After all, “institutions” are simply governance mechanisms with some degree of autonomy from both political and private interests. The gradual creation of institutions partially shielded from political power must become central to the development of an optimal mode of regulatory governance. The article presents suggestions for establishing accountability in regulatory governance, in particular by creating an internal control system based on a rotating board with representatives of users, producers, and civil society, in a process involving frequent reporting and disclosure.